Indigenous Youth Conflict Intervention: The Transformation of Butterflies - Cormier, Paul (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
The purpose of this article is to discuss the impacts of structural violence and its effects on Indigenous Peoples using Aboriginal People – The Indigenous Peoples of Canada, and the Canadian education system as the context for discussion. Due to the root causes of conflict and the nature of violence in Aboriginal contexts being structural, working towards positive peace based on a concept of human security is the best approach to managing Aboriginal youth violence. This approach is conducive to building a culture of peace which is consistent with Indigenous traditions. Alternative methods of formal education should be considered in Aboriginal / Indigenous contexts. These methods should be grounded in the traditions of local Indigenous groups providing a safe space for rediscovery and identity negotiation between tradition and contemporary society. The ability for Indigenous peoples to further their formal education has a profound impact on long term peace building activities. The link between education, poverty, and violence must be of primary consideration when designing peace building activities where Indigenous Peoples are involved.